Discourse markers in interaction from production to comprehension - Cuenca, Maria Josep 1964-; Degand, Liesbeth 1967- (Trends in linguistics. Studies and monographs, 2022)
The aim of this volume is to bring together researchers interested in investigating the role that Discourse Markers play in language production and comprehension from an experimental or corpus-based perspective. In any kind of human communication, Discourse Markers are part of the game. This omnipresence informs us of a crucial inherent aspect of human language. Yet, as a linguistic category, Discourse Markers remain underdetermined. To gain deeper insight into this complex linguistic category, more systematic work is needed on the production and on the interpretation of Discourse Markers in a variety of situational settings, resorting to different methodological approaches. The contributions in this volume aim at drawing more attention to the double face of Discourse Markers, namely as signals intentionally used by the speaker to facilitate the addressee's interpretation of the discourse, but also as potential traces of the speaker's production difficulties. The combination of experimental and corpus-based approaches and the focus on processing of Discourse Markers in both production and comprehension makes this volume a unique contribution in answering the question why we use Discourse Markers in certain situations, but also when we do not